Laboratory Investigations into the Failure Mechanisms of New Yielding and Inflatable Rockbolts Under Axial and Shearing Loading Conditions - Li, Danqi; Ma, S.; Lane, Martin; Chang, Ping; Crompton, B.; Hagen, S.A. (2022)
Rockbolts are widely used in the tunnels and underground mining industry for support and reinforcement of the rock mass around the perimeter of the excavation. Better understanding of the load transfer mechanisms of rockbolts could improve rockbolt technology. Current rockbolt testing generally focuses on axial loading of the rockbolt, with shear loading of rockbolts only becoming more prevalent in the last 10–15 years. This research experimentally investigated the load-carrying capacity of five new rockbolts under axial and shear loadings, of which three were friction bolts and two were yielding bolts. Testing was undertaken using high strength concrete blocks to simulate a homogenous rock mass. The yielding style rockbolts provided considerably more tensile load capacity and deformation compared to the inflatable rockbolts; however, the inflatable rockbolts have the ability to deform significantly more in shear than in tension and have similar shear deformation as the yielding-style rockbolts. This research contributes to the understanding of the performance of the new inflatable and yielding rockbolts in different loading conditions and hence provided a benchmark for comparison with other existing friction and yielding bolts. Ultimately, the addition of these new rockbolts in the ground support community would give the site engineers more options to properly select the most suitable rockbolt under varying geotechnical conditions.